Radicalization: The Misconception of Religious Practices in Diversity - Siti Komariah (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
Diversity is a necessity that cannot be denied by anyone, diversity that is based on true differences should be responded to with an attitude of tolerance and view that all differences are the nature of life. However, a handful of people in the name of religion actually see diversity as a threat that is very counter to their views so that with the frontal dare to call for war against these differences. Diversity and religious life is a concept that not only cares for fellow human beings but also respects and protects what God has created as a form of obedience. Seeing from a number of radical groups acting in the name of religion and carrying out extreme actions, this article seeks to reveal how Islamic organizations view the problem. By using a qualitative approach and phenomenology technique, which was carried out through in-depth interviews with 5 informants with the background of the organization's organizers it was found that there were three phases of a person behaving radically. But in this article more emphasis on the first phase, namely sensitivity, because this phase is seen as a channel for the formation of radical ideology in a person. Expected implications, social awareness can be formed that radicalism can actually be prevented from the beginning, with the right approach and method, as described in this article